Development of Innovative Digital Learning Media Based on Arabic Matching Puzzle for Learning Nahwu and Shorof - Fatihah, Ainiyatul; Alfan, Muhammad; Mahliatussikah, Hanik (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2025)
This study aims to develop digital learning media based on an Arabic Matching Puzzle to support the learning of Nahwu and Sharaf in junior high school. The research addresses challenges such as complex material, low student engagement, and limited interactive resources. Using the ADDIE model, the development process included analysis of needs, design and creation of media, expert validation, and classroom implementation. Results show that the media is feasible and effective in improving students’ understanding, motivation, and participation in learning Nahwu and Sharaf. Teachers also responded positively, indicating that the application supports teaching goals and facilitates more interactive learning experiences. The findings suggest that digital media based on game approaches can be a valuable solution to enrich Arabic language learning. This application is recommended for broader use and further development, including potential integration of advanced features such as Artificial Intelligence to enhance personalization and adaptability to diverse student needs.